The effect of zinc to aluminium ratio on the properties of zinc-aluminium layered double hydroxide pamoate nanocomposite - Hussein, Mohd Zobir; Yahaya, Asmah; Zainal, Zulkarnain; Jubri, Zaemah (Universiti Putra Malaysia Press, 2005)
Layered organic-inorganic hybrid materials of Zn-Al-layered double hydroxide(LDH)-pamoate nanocomposite (ZAPR) was prepared by intercalating pamoate anion (PA) as an organic guest into the Zn-Al layered double hydroxide inorganic host by spontaneous self-assembly method. Various Zn/Al ratios (R = 2, 3, 4, 5, 6, 7 and 8) were used in the preparation of the materials with concentration of PA= 0.02 M and pH 7. The effect of various Zn/Al ratios on the properties of layered organicinorganic hybrid nanocomposite materials resulted in the enhancement of the interlayer spacing of the nanocomposites in the range of 17.8 to 18.9 Å, compared to 8.9 Å for the Zn-Al LDH with nitrate as the counter ion. This indicates that the pamoate ion was successfully intercalated into the interlayer spacing of Zn-Al layered double hydroxide. The carbon content obtained from CHNS analysis was found to be increased from 22.9 to 24.5 and 26.4 % as the Zn/Al ratio was increased from 2 to 3 and 5, respectively. The Zn/Al ratio in the final product, (Rf) is lower than the initial Zn/Al ratio (Ri) used in the mother liquor. The BET surface area increased from 90.1 to 112.0, 137.2 and 146.6 m2/g as the Zn/Al ratio increased from 4 to 5, 6 and 8, respectively.